2018
DOI: 10.3389/fimmu.2018.00333
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic Transcriptional Signatures of Steady-State and Pathogen-Induced Dendritic Cells

Abstract: Dendritic cells (DCs) are key directors of tolerogenic and immunogenic immune responses. During the steady state, DCs maintain T cell tolerance to self-antigens by multiple mechanisms including inducing anergy, deletion, and Treg activity. All of these mechanisms help to prevent autoimmune diseases or other hyperreactivities. Different DC subsets contribute to pathogen recognition by expression of different subsets of pattern recognition receptors, including Toll-like receptors or C-type lectins. In addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 152 publications
(162 reference statements)
3
16
0
Order By: Relevance
“…One of the first indications of potential pathways operating in professional antigen presenting cells [for the subtypes of DCs, the reader is referred to other reviews (68, 69)], was curiously obtained in a melanoma cell line. Grommé et al fractionated MelJuSo melanoma cells and identified HLA class I molecules in a fraction also containing acidic HLA class II loading compartments.…”
Section: Mhc Class I Recycling and Antigen Presentationmentioning
confidence: 99%
“…One of the first indications of potential pathways operating in professional antigen presenting cells [for the subtypes of DCs, the reader is referred to other reviews (68, 69)], was curiously obtained in a melanoma cell line. Grommé et al fractionated MelJuSo melanoma cells and identified HLA class I molecules in a fraction also containing acidic HLA class II loading compartments.…”
Section: Mhc Class I Recycling and Antigen Presentationmentioning
confidence: 99%
“…Greenberg, 2014). Immature DCs inherently express T-cell co-stimulatory molecules only weakly; thus, they are prone to inducing anergic T cells (Pletinckx et al, 2015;Vendelova et al, 2018). However, our data indicate that weak costimulation of T cells by iDCs alone is not sufficient to mediate T-cell hyporeactivity, because production of extracellular Ado by CD73 was mandatory.…”
Section: Discussionmentioning
confidence: 81%
“…We then subdivided each DC subset into CD86 low MHC class II low -immature DCs and CD86 high MHC class II high -mature DCs ( Figure 2A) (15). The frequency of mature DCs among CD11c +total DCs increased at days 0.5 and 1.5 pc compared to that in virgin mice, and then returned to the level observed in virgin mice on days 2.5 and 3.5 pc ( Figures 2B,D,E).…”
Section: Mature Dcs Increase After Coitus and Decrease To Non-pregnanmentioning
confidence: 93%
“…For instance, IDO-expressing DCs and plasmacytoid DCs (pDCs) act as tolerogenic DCs (tDCs) (4). These tDCs have been shown to possess the capability of immunoregulation by inducing Tregs, as well as T cell, anergy and deletion (6,14,15). However, few reports have examined the characteristics of uDC subsets in murine pregnancy (2,4,(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation